Malament-Hogarth Machines and Tait's Axiomatic Conception of Mathematics. - Berry, Sharon (Erkenntnis, 2014)
In this paper I will argue that Tait's axiomatic conception of mathematics implies that it is in principle impossible to be justified in believing a mathematical statement without being justified in believing that statement to be provable. I will then show that there are possible courses of experience which would justify acceptance of a mathematical statement without justifying belief that this statement is provable.